PEMBUATAN SNACK BAR MILLET SEBAGAI ALTERNATIF CEMILAN KAYA SERAT - Mutiara Nugraheni, Nur Hidayah (Prosiding Pendidikan Teknik Boga Busana, 2020)
Abstract For now, eat was not only to satisfy our stomache but the most important as a functional food. People will not consume food by its taste but also its health. Functional food for kind of snack bar products can be made by giving millet flour in its ingredients. Flour millet is from millet (Penicum milaceum). Millet didn't have gluten or gluten free. Its means millet was save for people who suffered celiac disease. Not only it, the teksture of millet flour was fleaky so you must know the maximum amount of millet flour added. Addition of millet flour will affect sensory of the snack bar. Keywords: functional food, millet, snack bar.